2023
DOI: 10.1111/jon.13158
|View full text |Cite
|
Sign up to set email alerts
|

The current state of spinal cord functional magnetic resonance imaging and its application in clinical research

Grace Haynes,
Fauziyya Muhammad,
Ali F. Khan
et al.

Abstract: Since its development, spinal cord functional magnetic resonance imaging (fMRI) has utilized various methodologies and stimulation protocols to develop a deeper understanding of a healthy human spinal cord that lays a foundation for its use in clinical research and practice. In this review, we conducted a comprehensive literature search on spinal cord fMRI studies and summarized the recent advancements and resulting scientific achievements of spinal cord fMRI in the following three aspects: the current state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 121 publications
(764 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it is worth adding that examination of the spinal cord, especially when diagnosing CSM, may contribute to shortening the time of diagnosis and treatment. The authors emphasize that innovative research in the field of fMRI may contribute to the creation of new forms of patient treatment and the implementation of innovative diagnostic protocols [ 37 ]. In October 2023, Khan’s team and co-inventors presented a review on functional changes in the human brain in CSM patients using fMRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is worth adding that examination of the spinal cord, especially when diagnosing CSM, may contribute to shortening the time of diagnosis and treatment. The authors emphasize that innovative research in the field of fMRI may contribute to the creation of new forms of patient treatment and the implementation of innovative diagnostic protocols [ 37 ]. In October 2023, Khan’s team and co-inventors presented a review on functional changes in the human brain in CSM patients using fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is promise in research and advanced techniques in the field of MRI, which may improve the standards of care for people with CSM [ 43 ]. According to a review article by Haynes and co-authors, it can be concluded that further research in the field of fMRI of the spinal cord will contribute to the development of treatment for people with diseases in this area and will constitute the basis for implementing new assessment methods and developing treatment strategies [ 37 ]. However, the article by Khan and co-authors on the same topic gives great hope that the implementation of fMRI may facilitate the diagnosis of CSM.…”
Section: Future Directionsmentioning
confidence: 99%
“…This leaves room for interpretation of higher cortical regions connected to the spinal cord and involved in descending pain modulation. For more reviews on spinal and corticospinal imaging of pain, see Tinnermann et al (2021a) , Kinany et al (2022) , and Haynes et al (2023) .…”
Section: Applications Of Corticospinal Imagingmentioning
confidence: 99%
“…Recently, the findings of this study were replicated using an innovative data-driven multivariate approach ( Kinany et al, 2023 ) which shows great promise to probe CNS signatures of human sensorimotor behavior in health and disease. For more reviews on spinal and corticospinal imaging of motor task activity, see Landelle et al (2021) , Kinany et al (2022) , and Haynes et al (2023) .…”
Section: Applications Of Corticospinal Imagingmentioning
confidence: 99%
“…Functional MRI (fMRI) has been increasingly applied in the spinal cord to non-invasively map spinal cord neuronal function (Cohen-Adad, 2017; Haynes et al, 2023; Landelle et al, 2021; Powers et al, 2018). Spinal cord fMRI conducted in healthy volunteers have investigated neuronal activation induced by a wide range of tasks and stimuli, including upper extremity motor task (Govers et al, 2007; Kinany et al, 2019; Stroman et al, 1999; Weber et al, 2016b), thermal stimulation (Bosma & Stroman, 2015; Rempe et al, 2015; Weber et al, 2016a, 2018), tactile stimulation (Brooks et al, 2012; Kornelsen et al, 2013; Summers et al, 2010; Weber et al, 2020), noxious stimuli (Brooks et al, 2012; Summers et al, 2010; Tinnermann et al, 2021), and sexual arousal (Alexander et al, 2016; Kozyrev et al, 2012).…”
Section: Introductionmentioning
confidence: 99%